Korupce a podnikatelské objevování - Volejníková Jolana (Univerzita Pardubice, 2006)
Contribution named "Corruption and enterpreneurial detection" links up to Kirzner theory on the enterprise detection. His aim is to demonstrate , that in a society with increasing role of the state, come about the destruction of the enterprise detection process. Example of these destruction are activities like "rent seeking" and in consequence of a growing level of corruption in economic background. Block arises from the situation in Czech Republic.
Keywords: ekonomické myšlení; rakouská škola; podnikatelské objevování; teorie veřejné volby; Korupce; boj proti korupci